Respuesta :
[tex]f(x)=x^{3}-2x^{2}-6x+12 \\ \\ x^{3}-2x^{2}-6x+12=0 \\ \\ x^{2}(x-2)-6(x-2)=0 \\ \\ (x^{2}-6)(x-2)=0 \\ \\ (x- \sqrt{6})(x+ \sqrt{6})(x-2)=0 \\ \\ x- \sqrt{6}=0 \ \vee \ x+ \sqrt{6}=0 \ \vee \ x-2=0 \\ \\ x= \sqrt{6} \ \vee \ x=- \sqrt{6} \ \vee \ x=2 \\ \\ x\in \lbrace - \sqrt{6}, 2, \sqrt{6} \rbrace [/tex]
==================================
"Associate with people who are likely to improve you."
==================================
"Associate with people who are likely to improve you."